Mulheres e pombagiras nos terreiros Centro Espírita Pai Jeremias e Egbè Omorisà Sangò, em Cuiabá - MT - Carvalho, Heloisa Lima de (2018)
The purpose of this study was to understand the experiences of Camdonblé and Umbanda women practitioners, thinking about the relationships between women and Pombagiras discussing these relations through the interviews collected in two Terreiros (cult house of Afro-Brazilian religions) in Cuiabá, Mato Grosso, Brazil. In addition, it seeks to understand the gender relations into these religions, observing the intersections between gender, race/ skin color/ ethnicity and sexuality and deals with other issues like the link between Pombagira and the good or the evil. The aim is to make for an afrocentered reading of the Pombagira image, demystifying her association whit of evil, since she acts as intermediary of the love relationships linked to power, by sexuality, and combats the feminine role built in patriarchal society. Ethnopsychology is used, which allows the researcher, inserted in the Afro-Brazilian religious spaces, to take on the role of a consultant, making possible interpretations based on the interdisciplinary dialogue between Social Psychology and the Coloniality / Modernity Movement. The method used is narrative inquiry, which focuses on the human experience, facilitating the interaction between researcher and participants.